EVALUASI KEPUASAN MAHASISWA TERHADAP PEMBINAAN SOFT SKILL PADA PROGRAM STUDI PGMI FTIK IAIM SINJAI - Nurul Islamiah; Nurjannah Nurjannah; M. Mailhuddin (Jurnal Evaluasi Pendidikan, 2022)
This research is a descriptive study using quantitative methods. Quantitative research involves measuring the level of a particular trait. The subjects of this study were all students in the Madrasah Ibtidaiyah Teacher Education Study Program. Data collection techniques using questionnaires and documentation. Based on the results of the overall evaluation, information was obtained that of the 72 students who filled out the questionnaire, as many as 11.63% of students felt that the soft skills service was very satisfactory, 58.68% was satisfactory, 26.39% was unsatisfactory and there were 3.30% students who judged that the service was unsatisfactory. In other words, the largest percentage is in the satisfactory category. Therefore, student satisfaction with soft skills services in the Madrasah Ibtidaiyah Teacher Education Study Program is in the satisfactory category.